The industry engagement ladder. (3rd September 2020) - Rees, Dylan; Wang, Qiru; Laramee, Robert S.
Abstract : Purpose: This paper is a response to a frequently asked question from prospective industry partners searching for opportunities to collaborate with the Computer Science Department of Swansea University, UK. This paper seeks to provide structured guidance in the form of what is titled the Industry Engagement Ladder. Design/methodology/approach: The Industry Engagement Ladder presents a selection of collaboration opportunities, outlining the possible cooperation mechanisms between an industry partner and the academic institution. Findings: Opportunities are described and ranked according to the amount of investment required by the industrial partner, and therefore risk, from low to high. Originality/value: This concise paper provides a quick reference for perspective industry academia collaboration opportunities, the risks involved with each, the possible funding available to help foster these partnerships and the benefits to industry. These collaborative activities (and variations thereof) can be incorporated by any university department. The manuscript offers an ideal starting point for industry–university collaboration.